Android-Based Digital Teaching Materials In Table Tennis Learning - Adi, I Putu Panca; Ni Putu Dwi Sucita Dartini; Luh Putu Spyanawati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
The development of information technology in the form of smartphone development has opened up new opportunities in the world of education by developing models, teaching materials, digital-based media including in table tennis learning. The purpose of this study was to develop android-based digital teaching materials on table tennis learning. The research method uses Research and Development (R&D) with the development model by Borg and Gall. The subjects of this study were students of the Physical Education, Health and Recreation Study Program, FOK Undiksha who took the TP course. Table Tennis Learning. Data collection methods using documentation, interviews, and questionnaires. The data analysis technique used is descriptive analysis and qualitative analysis. The results showed that android-based digital teaching materials on table tennis learning have been developed. The product was declared suitable for use as teaching material for table tennis learning by experts with an average score of 94.08 in the very feasible category. The results of the practicality test showed an individual test with the results of 96 very good categories and the results of small group trials were 99 very good categories. It can be concluded that android-based digital teaching materials on table tennis learning are feasible and practical for use in TP courses. Table Tennis Learning for Physical Education, Health and Recreation Study Program students, FOK Undiksha.